2019
DOI: 10.1175/jpo-d-18-0144.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Physics of the Warm Water Volume and El Niño/La Niña Predictability

Abstract: Previous work has shown that warm water volume (WWV), usually defined as the volume of equatorial Pacific warm water above the 20°C isotherm between 5°S and 5°N, leads El Niño. In contrast to previous discharge–recharge oscillator theory, here it is shown that anomalous zonal flow acceleration right at the equator and the movement of the equatorial warm pool are crucial to understanding WWV–El Niño dynamics and the ability of WWV to predict ENSO. Specifically, after westerly equatorial wind anomalies in a coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This asymmetric occurrence implies that both opposite PSH forces that are exerted on the formation of El Niño and La Niña must be unequal. Similar results can also be found in the article of Clarke and Zhang (2019). The Pacific topography might mainly be responsible for this situation.…”
Section: The Respective Characteristics Of the Formation Of El Niño Asupporting
confidence: 88%
“…This asymmetric occurrence implies that both opposite PSH forces that are exerted on the formation of El Niño and La Niña must be unequal. Similar results can also be found in the article of Clarke and Zhang (2019). The Pacific topography might mainly be responsible for this situation.…”
Section: The Respective Characteristics Of the Formation Of El Niño Asupporting
confidence: 88%
“…As demonstrated in Clarke and Zhang (2019), the seasonal phase locking of ENSO is fundamental to its development and prediction. To quantitatively illustrate this characteristic, the empirical orthogonal function (EOF) analysis is conducted to the seasonal variation (i.e., from May to the following April for each year) of the observed Niño3.4 index,…”
Section: Connection Between the March Information And The Following Ementioning
confidence: 99%
“…Some aspects of ENSO, however, are not explained by the RDO theory such as (ii) the asymmetry between the magnitude of the WWV recharge preceding El Niño events compared to the magnitude of WWV discharge preceding La Niña events (e.g., Meinen and McPhaden 2000;Clarke and Zhang 2019); (ii) the asymmetry in duration and phase change transition with El Niño events lasting a shorter period and having a stronger tendency to be followed by La Niña events than vice versa (e.g., Kessler 2002;Larkin and Harrison 2002;Okumura and Deser 2010;Guan et al 2019;Clarke and Zhang 2019); 3) the decrease observed in WWV/ENSO SST lead time from around three seasons in the 1980s and 1990s to only one season during the post-2000 period (McPhaden 2012;Horii et al 2012;Bunge and Clarke 2014); and 4) the existence of different ENSO types: central Pacific (CP; with maximum SST anomaly found in the central equatorial Pacific) versus eastern Pacific (EP; with maximum SST anomaly found in the eastern equatorial Pacific) ENSO events (e.g., Kao and Yu 2009;McPhaden et al 2011;Singh and Delcroix 2013). Moreover, the RDO theory considers only the adjusted oceanic response, which occurs when wind-forced equatorial Kelvin waves (KWs) have left the WWV region via the eastern boundary and wind-forced off-equatorial Rossby waves (RWs) reflect at the western boundary into the WWV region [for a more detailed understanding of the connection between Sverdrup transport as considered in Jin's (1997) RDO theory and wave dynamics as considered in this study, see section 1.5.2 in Neske (2019)].…”
Section: Introductionmentioning
confidence: 99%
“…An emphasis on considering wind stress curl for ENSO dynamics was given by Clarke et al (2007), who theoretically derived WWV changes by wind stress curl at 58 latitude, which has a correlation of 0.85 to observed WWV changes between 1993 and 2001. However, when later developing their conceptual model of ENSO, Clarke et al (2007) instead utilize the relationship between wind stress curl derived WWV and Niño-3.4 SST (correlation 5 0.77) rather than wind stress curl itself. Thus, the developed conceptual model leaves out the possibility of strong equatorial wind stresses during ENSO events with weak wind stress curls around the boundaries of the WWV region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation